Recreational boaters' preferences for boating trips associated with offshore wind farms in US waters. (December 2020) - Dalton, Tracey; Weir, Michael; Calianos, Aislyne; D'Aversa, Nelle; Livermore, Julia
Abstract: This study used a stated preference approach to assess potential impacts of offshore wind farms on recreational boaters in and around Rhode Island (US) waters. To develop the stated preference survey, seven focus groups were conducted with recreational boaters in Rhode Island (RI) in 2017. A combined mail and on-line choice experiment survey was administered in the spring and summer 2018 to 2500 owners of US Coast Guard-documented recreational vessels with a hailing port in Rhode Island. The survey instrument elicited recreational boaters' preferences for particular attributes of a recreational boating trip (location, proximity to a wind farm, amount of nearby boating activity, main activity during trip, trip costs). Data were analyzed using the mixed logit model to understand how changes in individual attributes affect the acceptability of a boating trip. Findings indicate that the value of a recreational boating experience is considerably reduced in areas with offshore wind farms. Findings from this study provide valuable insights into the potential impacts of the growing offshore wind industry on one group of marine resource users and potential management strategies for addressing these impacts in the US. Highlights: Boating near an offshore wind farm, i.e. within 100 ft, detracts from a boater's experience. Boaters who fish are less negatively impacted by boating near a turbine than boaters who do not fish. Value of a recreational boating experience is affected by location, boats encountered, proximity to offshore wind farm, and activities during a trip.